Integration auf Zeit für ein Leben in Transition: Gesellschaftlicher und politischer Umgang mit den Herausforderungen einer segmentierten städtischen Migrationsgesellschaft in Muscat (Oman) - Deffner, Veronika; Pfaffenbach, Carmella (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
The contribution examines the issue of international migration and integration from an “alternative” perspective to broaden the view of the social and political challenges discussed to date. The coexistence of heterogeneous groups in urban space is discussed taking the example of Muscat, the capital of the Sultanate of Oman. Since the process of modernization commenced in 1970, the urban society in Muscat has gradually developed into a segmented immigrant society. The special feature of this young, dynamic immigration society is that Oman does not envisage the (permanent) integration of transnational migrants, nor do the latter. Therefore we regard temporary integration as an alternative pattern of social coexistence taking the different perspectives of the parties concerned into account. First, a couple of conceptual observations on an analysis of integration will be offered. Then, the general social and political framework conditions that regulate the working situation of foreigners in Oman—i.e. the sponsorship system and the policy of Omanisation—will be addressed. Building on this, the contribution will go on to discuss the migrants’ expectations and opportunities concerning integration based on spatial practice, taking as examples the two central aspects of the choice of place of residence and mobility opportunities. The socio-economic position of employees and recognition based on their professional and educational status prove to be the key criteria in this respect.
Keywords: transnational migration; labor migration; integration; segmentation; spatial practice; Oman